Types of Motivating Operations in Interventions With Problem Behavior: A Systematic Review. (January 2013) - Simó-Pinatella, David; Font-Roura, Josep; Planella-Morató, Joaquima; McGill, Peter; Alomar-Kurz, Elisabeth; Giné, Climent
A motivating operation (MO) alters both the effectiveness of a stimulus as a reinforcer and the current frequency of all behavior that has been reinforced by that particular stimulus. This article reviews studies that have manipulated a MO during interventions with school-age participants with intellectual disabilities and problem behavior. A systematic review was conducted using the following major electronic databases: PsychInfo, Education Resources Information Center, Science Direct, Blackwell, SAGE, and Medline. A total of 31 published articles representing 55 participants was examined. Findings from this study suggest that the modification of a MO usually has an effect on the problem behavior by either establishing or abolishing its motivation. Furthermore, a relationship was found between the type of MO and the behavioral function identified. The theoretical and practical implications of these findings, limitations of this study and potential issues for future research are discussed.